Trade and structural adjustment embracing globalisation. - ProQuest (Firm) (Paris : OECD, 2005)
This publication identifies the requirements for successful reallocation of labor and capital to more efficient uses in response to the emergence of new sources of competition, technological change and shifting consumer preferences. At the same time, it focuses on limiting adjustment costs for individuals, communities and society as a whole. Based on specific sectoral case studies, this volume includes analysis of the adjustment challenge and policy framework in both developed and developing countries, together with practical recommendations for good practice.--Publisher's description.
pt. 1. Structural adjustment : challenges and policy responses. The adjustment challenge -- The domestic policy framework : the experience of OECD member countries -- Trade and structural adjustment : towards good practice -- pt. 2. Sectoral case studies. Agriculture -- Fisheries -- Textiles and clothing -- Steel -- Shipbuilding -- Motor vehicles -- Health services -- International sourcing of IT and business process services.
Includes bibliographical references (p. 319-339).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2018. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Structural adjustment (Economic policy); International trade; Globalization -- Economic aspects; Electronic books